Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I've already confirmed that the following expression is true with a truth table, but I need to prove this with other Boolean expressions for my assignment. The $\oplus$ symbol is exclusive or in this case.

$f \oplus (g \oplus h)=(f \oplus g) \oplus h$

I have been messing around with little expressions for a while trying to get a start on proving this, but I've not really made any progress.

share|cite|improve this question
up vote 2 down vote accepted

Recall, you need "or", "not", and "and" to express the "exclusive or":

$f\oplus g$ means ($f$ or $g$) and NOT ($f$ and $g$):

$$f\oplus g \equiv (f\lor g) \land \lnot (f \land g)$$

Using $\;'\cdot\,'\,\text{ for}\; \land,\;\; '+\,'\,\text{ for}\,\,\lor\; \text{ and}\;\, \,'\, \text{ for}\;\,\lnot:$

$$f \oplus g = (f + g)\cdot(f\cdot g)'$$

Now extend that to three arguments

Expand $f\oplus(g\oplus h)$, and manipulate the expansion to obtain $(f\oplus g)\oplus h$

share|cite|improve this answer

You can can rewrite the $\oplus$ in terms of "not" and "or". Then, it should be easy to follow the logic.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.